Improving Performance Of Innovative Workforce In Malaysian Enterpreneurial SMES - Moslehi, Mohammad Mahdi (2011)
The main purpose of this study is to increase individual performance by concentrating on influential factors in the development of innovative workforce in Malaysian Entrepreneurial SMEs. The independent variables are transformational leadership, rewards, autonomy and empowerment and dependent variable is individual performance. This study uses the quantitative approach. It is a cross-sectional correlational study. The survey method is used to collect data.